Comparative Simulation Study of Impedance Enhancement in a Circular UWB Antenna Using Defected Ground Structure and Slot Techniques - Afiyah Nikmah; Arum Vonie Rachmawati; Muhimmatul Khoiro; Yohanes Galih Adhiyoga; Nanang Winarno; Rohim Aminullah Firdaus (Indonesian Review of Physics, 2025)
This study presents a comparative simulation analysis of impedance enhancement in a circular UWB microstrip antenna using Defected Ground Structure (DGS) and slot techniques. Three antenna configurations were investigated: a baseline circular antenna, a DGS-loaded antenna, and a combined DGS-slot antenna. All antenna models were designed and simulated using CST Studio Suite with identical simulation conditions to evaluate the progressive effect of each structural modification. The antenna performance was analyzed in terms of S11, VSWR, input impedance, realized gain, radiation efficiency, and radiation pattern. The results show that the combined DGS-slot antenna provides the best impedance-matching performance, achieving S11 below -10 dB from approximately 1.72 GHz to 13.06 GHz, corresponding to a continuous bandwidth of 11.34 GHz. This represents a bandwidth improvement of approximately 223.6% compared with the baseline antenna and 69.3% compared with the DGS-loaded antenna. The optimized antenna also achieves a minimum VSWR of approximately 1.01 at 7.66 GHz and an input impedance of 50.46 + j0.35 Ω near resonance. In addition, the antenna provides a realized gain of 4.735 dBi and radiation efficiency of 79.27% at 7.6 GHz. These results demonstrate the synergistic effect of DGS-slot coupling in improving impedance matching, bandwidth continuity, and radiation performance of circular UWB antennas